The monetary circulation of Moesia Inferior from the beginning of the 2nd century AD to the end of the 3rd century AD - Bonchev, I (2018)
This thesis intends to gather and analyse all coin hoards and the majority of the single finds found on the territory of Moesia Inferior, dated between AD 100 and 300. The study will demonstrate how coins, through their existence as archaeological objects, offer profound insights not only into the matters of economy, state organization, and monetary supply but also into the local history of the cities which operated as mints. This study attempts to build a new and detailed framework for studying and interpreting coin assemblages in this area of Europe. A major aim is to create a fundamental basis for future research in the province so every new hoard or stray find can be added to the database which will allow large-scale analysis; this database will facilitate the incorporation of Lower Moesia into the numismatic map of the Roman Empire.